Ocular Biometry and Ophthalmic Parameters of Normal Eyes in French Bulldog Healthy Dogs - Andrade, Talita Franco [UNESP]; Moreno, LuízA Rodrigues Dale Vedove; Nasomento, Felipe Franco; Passareli, João Victor Goulart Consoni; dos Santos Rosa, Vinícius; da Silva Santos, Thais Caroline; Brinholi, Rejane Batista; Andrade, Silvia Franco (Research Links, 2021)
The objective was to perform ocular biometry and ophthalmic examination in dogs of the French Bulldog breed. We evaluated 72 normal eyes of 36 healthy French Bulldog dogs, 20 males and 16 females, aged from 1 to 7 years. Ocular ultrasound was performed in B mode with a 10 MHz linear probe, and the following parameters of ocular biometry were evaluated: horizontal axial diameter (HAD) of the eye, lens thickness (LT), anterior chamber depth (ACD), and vitreous chamber depth (VCD). The ophthalmic exams performed were as follows: Schirmer Tear Test-1 (STT-1), rebound tonometry (Tonovet), Tear Film Break-up Time (TBUT), and Fluorescein Test (FT). The ocular biometry results (mean±SD) in millimeters were: 20.5 ± 0.6 (HAD), 3.8 ± 0.4 (ACL), 7.4 ± 0.3 (LT) and 9.4 ± 0.4 (VCL), and from the ophthalmic exams (mean±SD) were: 24 ± 3.7 (16.5-33.5) mm/min (STT-1), 20.0 ± 3.7 (13.5-27.0) mmHg (rebound tonometry), and 24.4 ± 6.3 (16–40) seconds (TBUT), and FT was negative in all dogs. The obtained results can serve as parameters of normal values of ocular biometry and ophthalmic exams for ambulatory routines, intraocular surgeries, and future ophthalmic studies in this breed.
Keywords: Dogs; French Bulldog; Ocular biometry; Ocular ultrasound; Ophthalmic exams